Environmental Health Disparities in Housing - Jacobs, David E. (American journal of public health (1971), 2011)
The physical infrastructure and housing make human interaction possible and provide shelter. How well that infrastructure performs and which groups it serves have important implications for social equity and health. Populations in inadequate housing are more likely to have environmental diseases and injuries. Substantial disparities in housing have remained largely unchanged. Approximately 2.6 million (7.5%) non-Hispanic Blacks and 5.9 million Whites (2.8%) live in substandard housing. Segregation, lack of housing mobility, and homelessness are all associated with adverse health outcomes. Yet the experience with childhood lead poisoning in the United States has shown that housing-related disparities can be reduced. Effective interventions should be implemented to reduce environmental health disparities related to housing.